Crystal structure of O-hexyl benzoylcarbamothioate, C14H19NO2S - Caracelli, Ignez; Zukerman-Schpector, Julio; Garcia, Ariel L. L.; Alvarez, Heiddy M.; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C14H19NO2S, monoclinic, P21/c (no. 14), a = 8.6849(10) Å, b = 18.740(2) Å, c = 10.0465(12) Å, β = 112.845(3)°, V = 1506.9(3) Å3, Z = 4, Rgt(F) = 0.0685, wRref(F2) = 0.2023, T = 293(2) K.